SUBORDINASI PEREMPUAN DAN IMPLIKASINYA TERHADAP RUMAH TANGGA - Syafe’i, Imam (Analisis: Jurnal Studi Keislaman, 2015)
THE SUBORDINATION OF WOMEN AND ITS IMPLICATION TO HOUSEHOLD: Women in general are in the oppressed, persecuted  and deprived.  Islam teaches  the  respect  feeling and cherishes one other. This paper examines the perspective of feminism. The subordination of women is rooted in a set of constraints   and  cultural  practices  that  hinder  women’s  access to the opportunity to compete fairly with men. This process happened   through   the   customs   in   the   family,   community, education institutional that provide the role to place the women in number 2 in public. Therefore, the women leadership in domestic and  public  area  can’t  be defined  as  the  superior  especially  in physically sense but also it can be interpreted  the capability  of the women. So, basically everybody has the ability to be a leader. This thing continued to be done by the group of feminism in spite of getting  challenges and some obstacle  of the group that  focus on the patriarchal  culture and religion with the understanding  of religious –legal- formal. The group aligns the role of women by men so that there is no subordination,  marginalization,  violence, persecution  and injustice  which have covered the independence of the rights of women.